(untitled) (KYAMC Journal, 2013)
Corticosteroids are often used as an adjunct in the treatment of various forms of tuberculosis (TB) and for the prevention of complications, such as constrictive pericarditis, hydrocephalus, focal neurological deficits, pleural adhesions, and intestinal strictures. Notwithstanding, they have been proven in clinical trials to improve the following outcomes only death or disability in human immunodeficiency virus (HIV)-seronegative patients with tubercular meningitis and tubercular pericarditis. Despite a lack of specific evidence for efficacy in HIV co-infected patients with tubercular meningitis or pericarditis, corticosteroids are generally recommended in them as well. Corticosteroids significantly decrease the risk of pleural thickening in patients with tubercular pleural effusion; the clinical significance of this finding, however, is unclear. Recently, it has been demonstrated that use of corticosteroids improves the morbidity in HIV co-infected patients with paradoxical TB immune reconstitution inflammatory syndrome (IRIS). However, evidence favouring the use of corticosteroids in other clinical situations is sparse or lacking. Likewise, the biological mechanisms underlying their beneficial effect in TB meningitis and pericarditis remain poorly understood. DOI: http://dx.doi.org/10.3329/kyamcj.v2i2.13265 KYAMC Journal Vol.2(2) January 2012, 198-204